Retention of sulfate and chloride ions in commercially available tubular membranes - Qadir, D. (Techno Press, 2017)
Performance evaluation of four commercially available tubular membranes (AFC 80, AFC 30, PU 608, ES 404) was accomplished in self-assembled membrane testing unit. Effects of varying transmembrane pressure, feed concentration and anion type were investigated. Aqueous solutions of salts such as calcium chloride, calcium sulfate, tin chloride and tin sulfate were prepared for this study. It was noted that the investigated parameters e.g., pressure and concentration had significant effects on membrane's performance. Nevertheless, anion type effectively played its role in the rejection of salts since salt having SO4-2 anions had a better rejection than the salts containing Cl-1. It is observed that rejection was dominated by Donnon exclusion for strongly charged nanofiltration membranes whereas for weakly charged ultrafiltration membranes, size exclusion was the key mechanism to reject the ions. © 2017 Techno-Press, Ltd.